Restoring the Lost Constitution : The Presumption of Liberty - Updated Edition - Barnett, Randy E. (Book collections on Project MUSE., 2014)
The U.S. Constitution found in school textbooks and under glass in Washington is not the one enforced today by the Supreme Court. In Restoring the Lost Constitution, Randy Barnett argues that since the nation's founding, but especially since the 1930s, the courts have been cutting holes in the original Constitution and its amendments to eliminate the parts that protect liberty from the power of government. From the Commerce Clause, to the Necessary and Proper Clause, to the Ninth and Tenth Amendments, to the Privileges or Immunities Clause of the Fourteenth Amendment, the Supreme Court has rendered each of these provisions toothless.